Profitability Moderates The Effect Of Capital Structure On Financial Distress: A Trade-Off Perspective - Seandy Ginanjar; Wawan Ichwanudin (Universitas Indonesia Membangun (Inaba), 2026)
This study examines the moderating role of profitability in the relationship between capital structure and financial distress from the perspective of trade-off theory. The sample comprises firms consistently included in the LQ45 Index during 2021–2024, with observations structured as firm-year panel data. Capital structure is measured by the debt-to-equity ratio, profitability by return on assets, and financial distress by the Altman Z-Score. Hypotheses are tested using panel-data regression and Moderated Regression Analysis estimated through the Random Effects Model at a 5 percent significance level. The results show that the debt-to-equity ratio has a negative and significant effect on the Z-Score, indicating that higher leverage increases financial-distress risk. Return on assets does not exert a significant direct effect on the Z-Score. However, the interaction between leverage and profitability is positive and significant, demonstrating that profitability weakens the adverse effect of debt on financial condition. Firms with stronger profitability are therefore better able to absorb debt-related pressures, whereas highly leveraged firms with lower profitability remain more vulnerable to financial distress. These findings provide empirical support for the contingent trade-off between the benefits of debt financing and the potential costs of financial distress and extend evidence concerning capital structure decisions in emerging markets.